Training foreign language teachers - Wallace, Michael J. (Cambridge University Press, 1991)
Training Foreign Language Teachers is aimed at anyone in the area of foreign language teaching who is engaged in designing, running or taking part in teacher education programmes. It begins by examining some current models of teacher education. It goes on to describe the notion of the teacher as 'reflective practitioner' - someone who reflects on the practice of their profession as a way of developing their expertise in it. Training Foreign Language Teachers explores ways in which a reflective approach can be applied to many areas of the teacher education programme, including: * classroom observation * microteaching * design and assesment of teacher education programmes. It contains many suggestions for practical work and discussion, and numerous applications to actual situations, including an extended case-study